2017
DOI: 10.1111/psyp.12831
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity from stimuli that are not perceived: Visual mismatch negativity during binocular rivalry suppression

Abstract: Predictive coding explains visual perception as the result of an interaction between bottom‐up sensory input and top‐down generative models at each level of the visual hierarchy. Evidence for this comes from the visual mismatch negativity (vMMN): a more negative ERP for rare, unpredictable visual stimuli—deviants, than for frequent, predictable visual stimuli—standards. Here, we show that the vMMN does not require conscious experience. We measured the vMMN from monocular luminance‐decrement deviants that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 77 publications
4
11
0
Order By: Relevance
“…However, they differed in how they interacted with awareness and the task. The vMMN was observable independently of these factors, which is in line with prior findings showing nonconscious effects between deviant and standards during binocular rivalry (Jack et al, 2017). Thus, the current study adds new evidence that the vMMN can also be elicited in this novel and ecologically valid no-report IB paradigm.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, they differed in how they interacted with awareness and the task. The vMMN was observable independently of these factors, which is in line with prior findings showing nonconscious effects between deviant and standards during binocular rivalry (Jack et al, 2017). Thus, the current study adds new evidence that the vMMN can also be elicited in this novel and ecologically valid no-report IB paradigm.…”
Section: Discussionsupporting
confidence: 91%
“…Although there is evidence for a nonconscious MMN, the P3 to deviant stimuli seems to be elicited only during conscious processing (Bekinschtein et al, 2009;Faugeras et al, 2012;Strauss et al, 2015;Jack et al, 2017; but see Silverstein et al, 2015). This outcome accords with the proposal that awareness and the emergence of a P3 are strongly associated (Dehaene et al, 2006(Dehaene et al, , 2014.…”
Section: Introductionsupporting
confidence: 81%
“…Fig 2B shows that there were positive voltages at right occipital electrodes for the P1, whereas for the N1, there were negative voltages at right occipital electrodes and positive voltages at fronto-central electrodes. We consistently see this right-hemisphere bias in many of our binocular rivalry and ERP studies [ 43 , 45 , 92 , 110 ].…”
Section: Resultssupporting
confidence: 58%
“…Does the oblique effect require visual consciousness? Recently, Takács et al [ 91 ] found that infrequent and unpredictable changes in the orientation of task-irrelevant gratings elicited a bigger visual mismatch negativity (vMMN), an ERP component thought to index pre-attentive visual change detection [ 92 94 ], from cardinal gratings than from oblique gratings. They concluded that the oblique effect does not require attention.…”
Section: Introductionmentioning
confidence: 99%
“…One main characteristic of the MMN is that it is elicited irrespective of whether the participants are attending to the stream of presentation or become aware of the deviation. While this was extensively demonstrated in the auditory modality (see Näätänen et al, 2007 ), there is increasing evidence that the MMN also mirrors automatic and pre-attentive change detection in the visual modality (Berti, 2011 ; Flynn et al, 2017 ; Jack et al, 2017 ). The second main feature is that the MMN is often followed by a frontal P3 or P3a (for instance, when the deviants become task-relevant).…”
Section: Introductionmentioning
confidence: 97%